Cost effectiveness and quality of life assessment on dental filling and tooth extraction in Balongsari Public Health Center - Taufan Bramantoro; Thinni Nurul R (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Dental health services program implementation in Balongsari Public Health Center during three years, 2006 until 2008, have a high average ratio of filling treatment compared to tooth extraction treatment (1:1.79) as compared to the standard set by the Ministry of Health (1:1). Cost effectiveness analysis and quality of life is needed as a form of economic evaluation of costs incurred by the consequences or impacts of health care programs, especially dental filling and tooth extraction, use to help in supporting the process of policy making in health care. The objective of this study was to assess cost effectiveness analysis (CEA) and quality of life (QoL) on dental filling and extraction treatment in Public Health Center. Methods: The study was conducted on 31 respondents who received filling treatment and 38 respondents who received tooth extraction. All of the respondents carried out to evaluate the total costs incurred in obtaining treatment and QoL between before and after treatment, which consist of the physical aspects, psychological, social, and economic. Results: The average total cost of dental filling treatment of the 31 respondents was Rp. 27,934.45, and in tooth extraction of the 38 respondents at Rp. 22,406.83. The average difference in the QoL, before and after dental filling treatment amounted to 121.25. In extractions, QoL difference in value before and after treatment at 132.36. Cost effectiveness ratio value in dental filling treatment amounted to 230.37, and in tooth extraction at 169.63. Conclusion: It is concluded that cost effectiveness ratio in the filling treatment is higher than the extraction, that the tooth extraction treatment is considered more cost effective than filling treatment.Latar belakang: Pelaksanaan program pelayanan kesehatan gigi di Puskesmas Balongsari selama tiga tahun, yaitu tahun 2006 hingga 2008, memiliki rata-rata rasio perbandingan perawatan tumpatan dengan pencabutan gigi (1:1,79) yang lebih tinggi dibandingkan dengan standar rasio yang ditetapkan oleh Kementerian Kesehatan (1:1). Analisis efektifitas biaya dan kualitas hidup, dibutuhkan sebagai bentuk dari evaluasi secara ekonomi, dilihat dari biaya yang dibandingkan dengan dampak program pelayanan kesehatan, khususnya perawatan tumpatan dan pencabutan gigi, untuk mendukung proses pengambilan kebijakan dalam pelayanan kesehatan. Tujuan: Tujuan penelitian ini adalah untuk menilai cost effectiveness analysis (CEA) dan quality of life (QoL) pada perawatan tumpatan dan pencabutan gigi di Puskesmas Balongsari. Metode: Penelitian ini dilakukan terhadap 31 orang pasien yang mendapatkan perawatan tumpatan dan 38 orang pasien yang mendapatkan pencabutan gigi. Pada seluruh responden dilakukan evaluasi total biaya yang dikeluarkan untuk mendapatkan perawatan dan pengukuran kualitas hidup sebelum dan sesudah perawatan, yang terdiri dari aspek fisik, psikologis, sosial, dan ekonomi. Hasil: Rata-rata total biaya perawatan tumpatan gigi dari 31 responden adalah Rp. 27,934.45, dan pada pencabutan gigi sejumlah 38 responden sebesar Rp. 22,406.83. Rata-rata nilai selisih QoL, sebelum dengan sesudah perawatan tumpatan gigi sebesar 121.25. Pada pencabutan gigi, nilai selisih QoL sebelum dengan sesudah perawatan sebesar 132.36. Nilai cost effectiveness ratio pada perawatan tumpatan gigi adalah sebesar 230.37, dan pada pencabutan gigi adalah sebesar 169.63. Kesimpulan: Dapat disimpulkan bahwa cost effectiveness ratio pada perawatan tumpatan gigi lebih tinggi dibandingkan pada pencabutan gigi, sehingga pencabutan gigi dinilai lebih cost effective atau efektif secara biaya, dibandingkan dengan perawatan tumpatan gigi.